TANTANGAN PENGEMBANGAN E-LEARNING KAMPUS MERDEKA BELAJAR - Razak Umar; Asna Usman Dilo; Titin Samsudin; Nurlina Rahman (Tadbir: Jurnal Manajemen Pendidikan Islam, 2024)
With the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) Curriculum in 2020, the opportunities for online learning, particularly through the utilization of e-learning, have significantly expanded. How prepared are universities to realize this MBKM initiative, and what challenges do they face? This research aims to construct the development of e-learning to accelerate the Merdeka Belajar – Kampus Merdeka (MB-KM) Program at IAIN Sultan Amai Gorontalo and UHAMKA Jakarta. This descriptive research employs a mixed-methods approach. Data collection techniques include observation, interviews, and Focus Group Discussions (FGD). Data is analyzed using reduction, display, and conclusion techniques. The research findings indicate that the implementation of MBKM at universities, whether face-to-face or online, can be achieved through student exchanges within the same or different universities, entrepreneurial activities, and thematic community service/fieldwork activities. The design of e-learning development to accelerate the implementation of MBKM can be initiated through: (a) ensuring the accessibility and stability of internet, electricity, telephone, and other infrastructure networks, (b) selecting reliable and modern hardware and software, (c) establishing a strong IT management institution with adequate operational funding, and (d) preparing professional human resources with a high work ethic. The next step is to enhance the performance of university e-learning and study programs in terms of content performance, accuracy, format, appropriateness, ease of use, security and privacy, and response speed